PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN SARANA PRASARANA TERHADAP KUALITAS PELAYANAN SKCK MELALUI KINERJA PETUGAS SKCK DI POLRES BOJONEGORO - jurnalmap map; Hariyanto ÔÇÄ; Hadi Susanto; Arini Sulistyowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The purpose of this study is to describe the effect of human resource and infrastructure competencies on the SKCK service quantity through the performance of SKCK officers at the Bojonegoro Regional Police Station. This type of research is explanatory research and the approach in this study uses a quantitative approach. The population in this study were with sampling technique was by accidental sampling with a total of 100 respondents as SKCK Service users. To conduct data analysis, it is carried out using path analysis. The results showed that competency, infrastructure, staff performance and service quality were in good condition. Competence has a significant influence on employee performance. Infrastructure has a significant influence on the performance of officers. Competence directly has a significant effect on service quality. Infrastructure directly has a significant influence on the quality of service. The performance of officers directly has a significant influence on the quality of service. Competence has a significant influence on service quality through the performance of officers. Infrastructure facilities have a significant influence on the quality of service through the performance of officers.Keywords: competence, infrastructure, performance, service quality